A Study of Hadiths About Riya' in the Book of Hidayatus Salikin Perspective of Abdul Samad Al-Falimbani - Aini, Mufidatun Nur; Halim, Nuruddin Ghilman; Muhid, M; Muthoharoh, Isnaini Luluatim (Suhuf: International Journal of Islamic Studies, 2024)
The Qur'an and hadith are the main guides for Muslims, but the temptation of lust sometimes leads humans to riya' behavior, which is doing good only for the praise of humans, not the pleasure of Allah. The book "Hidayatus Salikin" written by Abdul Samad al-Falimbani, is a phenomenal work that is quite calculated among Muslims. The figure with expertise in Sufism and philosophy more or less suggests practical applications in everyday life related to religious issues. Descriptive qualitative research method with content exploration in the book "Hidayatus Salikin". This article will present the concept of riya' from various scholars' perspectives and emphasize the importance of pure intention in worship. By focusing on the Hadiths of the Prophet Muhammad PBUH contained in the book "Hidayatus Salikin", this article provides an in-depth understanding of the dangers of riya' and the need to maintain sincere intentions, according to the teachings of the Qur'an and Hadith. Sheikh Abdul Samad al-Falimbani encourages Muslims to practice religion with purity of intention, avoiding riya', and following the guidance of the Qur'an and hadith.  Riya' or performing acts of worship for human praise is considered shirk khafi (hidden shirk). This discourse underscores the necessity for Muslims to cultivate purity of intention, thereby fortifying their spiritual endeavors against the insidious influence of riya'.